Peran Kepemimpinan Kepala Sekolah SMP Negeri 9 Talang Ubi Kabupaten Pali dalam Meningkatkan Efektifitas Kinerja Guru - Diwut Setiadi; Saipul Annur (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
In this study to find out the role of the Principal in improving the effectiveness of teacher work in SMP Negeri 9 Talang Ubi Penukal Abab Lematang Ilir District of South Sumatra Province and know the obstacles faced by the Principal in improving the effectiveness of teacher work in SMP Negeri 9 Talang Ubi. The focus of this research is the Role of the Principal including the Principal as Education Supervisor, Principal as Leader (Leader), Principal as Administrator, as well as the obstacles faced by the Principal in improving the effectiveness of work and quality of teacher resources. Primary data sources in the study included the Deputy Principal, teachers, the School Committee, and the parents of students, and students. Data collection techniques use three ways: observation, interview, and documentation. Data is analyzed using the Interactive Qualitative Data Analysis model. The results of the study showed that the principal of State Junior High School 9 Talang Ubi has carried out his role as administrator, supervisor, and leader well and the obstacles faced by the principal in improving the effectiveness of teacher work and human resources, namely unspent school facilities and infrastructure and incomplete human resources. The principal is an education leader who has a very large task and role in developing the quality of education in schools, the development of the spirit of work, harmonious cooperation on education.